Thermal neutron cross sections and diffusion parameters of diphenyl and dowtherm-A using a synthetic scattering function - Florido, P. C.; Gillette, Víctor Hugo; Granada, José Rolando (Comisión Nacional de Energía Atómica; Argentina)
Fil: Florido, P. C. Comisión Nacional de Energía Atómica; Argentina